Legal Existence of Local Wisdom for Bajo Fishery Tribe on Indonesian Maritime Border - Oheo Kaimuddin Haris; Syahbudin Syahbudin; Ahsan Yunus (Hasanuddin Law Review, 2019)
This work is aimed at exploring appropriate method in legitimating and admitting toward legal existence for Bajo effort’s local wisdom particularly in maintaining Indonesian’s Border. This effort is importance to maintain sovereignty of Indonesia's maritime boundaries without having to eliminate Bajo’s local wisdom that may exclude sustainable development for Bajo society. This situation has altered their traditions that they just initially and merely fished fishes just for consumption. For that reason, this work offers appropriate values in legitimating and admitting a legal existence for Bajo effort’s local wisdom such as the rights of traditional fisherman community of Bajo tribe in human rights law as indigenous people right based either on National and International Law and; the legal protection of Bajo communal rights in exploiting sea and traditional fisherman criteria after UNCLOS 1982 and MOU BOX 1974 including its amendments. The application of this method may create holistic and traditional manners in keeping and managing collective strategic resources for the greatest benefit for national defend especially for Bajo fishery tribe.